How to achieve top line profitable growth in the still water category for the brands Vitalis and Caramulo - Antunes, Beatriz (2018)
Leader in the beer market in Portugal, Super Bock Group is the second biggest player in the still bottled water category, owning two brands: Vitalis and Caramulo. With a past focus only on Vitalis, the company expressed concerns about Caramulo positioning in the market, leading to an interest in exploring new opportunities. By analysing the still bottled water industry, pinpointing the main trends, and evaluating the consumer’s habits and purchase behaviors, a growth opportunity was identified within the environmental and social sustainability; convenience; and beauty segments. The proposals for Vitalis, offer a solution to solve the goal established by SBG.